On Financing Retirement, Health, and Long-term Care in Japan - McGrattan, Ellen (IMF Working Papers; Working Paper ;, 2018)
Japan faces the problem of how to finance retirement, health, and long-term care expenditures as the population ages. This paper analyzes the impact of policy options intended to address this problem by employing a dynamic general equilibrium overlapping generations model, specifically parameterized to match both the macroeconomic and microeconomic level data of Japan. We find that financing the costs of aging through gradual increases in the consumption tax rate delivers a better macroeconomic performance and higher welfare for most individuals than other financing options, including those of raising social security contributions, debt financing, and a uniform increase in health and long-term care copayments.